Exploring the Relationship between Screen Time and Developmental Delays in Early Childhood - Ayaz, Muhammad; Juriasinghani, Manesha; Punshi, Monica; Kundi, Fatimah Karim; Nasir, Muhammad; Durrani, Hameed Mumtaz; A Gbamgbola, Taiwo; Sarwar, Benash (Journal of Neonatal Surgery, 2025)
Background: There is evidence that children's healthy development suffers when they spend more time in front of screens. Less is known regarding this connection in early infancy, in contrast to the majority of research that has concentrated on school-aged children. We set out to address this knowledge gap by investigating the link between preschoolers' screen usage and their developmental health. Objective: Determine the direction of the relationship between the amount of time spent in front of a screen and the outcomes of development among a set of mothers and their children. Methods: In this longitudinal cohort study 312 children and mothers were presented. The mothers' reports were used to assess the children's screen-time behavior (total hours per week) & their developmental results (Ages & Stages Questionnaire, Third Edition) at one, two, and three years age. In order to evaluate all of the data, SPSS 25.0 was utilized. Results: There were majority 178 (57.1%) males and 134 (42.9%) were female children.The results of a random-intercepts, cross-lagged panel model showed that there was a statistically significant correlation between higher levels of screen time at 2 and 3 years and worse performance on developmental screening tests at 3 years (β, −0.05; 95% CI, −0.8 to −0.02). Both of these within-person associations were time-varying, and they controlled for between-person differences. Conclusion: This study lends credence to the idea that screen usage has a direct impact on children's growth and development. In order to mitigate the negative effects of excessive use, it is recommended that family media planning be encouraged and that screen time be managed.